ANALISIS PENGUASAAN PENGGUNAAN KATA PREPOSISI â€œANZHAOâ€ DAN â€œGENJUâ€ PADA MAHASISWA BAHASA MANDARIN ANGKATAN 2015 - Septiani, Septiani; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstractâ€œanzhaoâ€andâ€genjuâ€both havethe meaning of a particular application or standards. However,if seen in terms of the use of the word,the two could not mutually replace.therefore,in the process of studying the â€œanzhaoâ€and â€œgenju,the studentsoften encounter errors when using both those words.in order to understand the conditions of mastery against the word preposition â€œanzhaoâ€andâ€œgenjuâ€on student education in chinese university of tanjungpura forces 2015,the authors examines how to use evaluation methods to implement test test to students.the results of his research,analysis of the mastery of the use of the Â word prepositionâ€anzhaoâ€on students language education in chinese university of tanjungpura 2015 sovereignty forces some very nice, 56.90% average Â and also against the studentâ€™s mastery of â€genjuâ€portion is Â not good,an average 48.76%.mastery of the students on the usage of Â the grammarâ€genju+...yijian/yaoqiu/diaoca/jingyan+zhuyuâ€is still very less,the reason is because the students are still less understand this Â grammar Â usage and also could distinguish the second words in the sentences.Keywords:Â Â Â Â Â Â  anzhaoï¼Œgenjuï¼Œmastery analysis